The operational role and the importance of the application of criminal procedures during the investigation of the organized crime in Kosovo - Maliqi, Reshat (Technium Social Sciences Journal, 2022)
The application of criminal procedures in the investigation of organized crime in Kosovo quests a deeper empirical study and wider research of a scientific literature than ever done before. The failure of many organized crime cases throughout the courts of Kosovo and the light and acquittal sentences are real indications that the application of criminal proceedings is not being properly conveyed in practice. The data provided through the empirical research of this paper indicate that non-compliance with criminal procedures leads to a decrease in efficiency and a significant increase in organized crime cases. Through this research we aim to identify the possible factors that affect the growth of the phenomenon of crime as well as the reflection of institutions dealing with the prevention and fight against crime. According to the observation the author suspects that the starting point of criminal proceedings regardless of the degree of probability is extremely important for the fight against crime, especially the fight against modern forms characterized by a high degree of organization, professionalism, specialization and secrecy. This paper reflects the detailed theoretical research of the scientific literature by various local and foreign authors and experts who have written about criminal procedures, research and analysis of theoretical and practical data on the meaning and importance of the implementation of criminal procedures in detecting organized crime in Kosovo are of particular importance to investigators of organized crime in the future. The effectiveness of criminal procedures in detection of organized crime in Kosovo should be closely related to criminology, criminalistics and criminal policy, the implementation of criminal procedures should in principle aim to return the basis of suspicion to the highest level of suspicion. This activity starts with the appearance of the basis of suspicion or the highest form of suspicion in the form of orientation and elimination indicators. The same activity consists of criminal control and processing. The content and strategy of these activities determine their further course, as well as condition the range of rules of criminal science in a specific case based on the provisions of the Code of Criminal Procedure, as well as other provisions of laws and bylaws. The strategy and tactics of these activities are dictated by the type of criminal offense.